2014
DOI: 10.13075/mp.5893.2014.008
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress and Psychosocial Risk Among Journalists

Abstract: The study results evidence that occupational stress experienced by journalists determine the risk of health self-assessment, satisfaction with work organization and interpersonal relationships. The presented outcomes indicate that regardless of the experienced stress level it is necessary to assess the psychosocial risk because even an average level of stressfulness could be associated with the risk of adverse consequences for employees in terms of their job performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In the process of doing their jobs, journalists are exposed to different levels of job risks that include threats to life, physical attacks, assault, harassment, and kidnapping of loved ones. Overall, evidence in the literature (Najder & Merecz-Kot, 2014;Talabi et al, 2021) classifies the job risks of journalists into physical and mental risks. Talabi et al (2021) examined 470 journalists in Nigeria and reported that they face physical and emotional job risks that make journalism practice difficult.…”
Section: Impact Of Job Risks On Journalistsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of doing their jobs, journalists are exposed to different levels of job risks that include threats to life, physical attacks, assault, harassment, and kidnapping of loved ones. Overall, evidence in the literature (Najder & Merecz-Kot, 2014;Talabi et al, 2021) classifies the job risks of journalists into physical and mental risks. Talabi et al (2021) examined 470 journalists in Nigeria and reported that they face physical and emotional job risks that make journalism practice difficult.…”
Section: Impact Of Job Risks On Journalistsmentioning
confidence: 99%
“…Talabi et al (2021) examined 470 journalists in Nigeria and reported that they face physical and emotional job risks that make journalism practice difficult. Najder and Merecz-Kot (2014) examined 211 journalists in Poland and reported that they face different psychological risks in the process of performing their duties that were considered higher than those of other occupations. Smith et al (2018) carried out a study to examine the impact of risky assignments on the posttraumatic stress disorder symptoms of journalists in the United States of America.…”
Section: Literature Reviewmentioning
confidence: 99%